2019
DOI: 10.1111/1759-7714.12984
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial NDUFA4L2 protein promotes the vitality of lung cancer cells by repressing oxidative stress

Abstract: Background Non‐small cell lung cancer (NSCLC) accounts for a significant proportion of cancer‐related deaths and lacks an effective treatment strategy. NSCLC tissues are generally found in a low oxygen environment. The NDUFA4L2 protein, located in the mitochondria, is encoded by the nucleus genome and is considered a crucial mediator that regulates cell survival. A better understanding of the mechanism of NDUFA4L2 in NSCLC survival in hypoxic environments is essential to design new therapeutic met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…For hepatocellular carcinoma, Sarathi et al found that NDUFA4L2, CRHBP and PIGU were main genes with monotonic changes of expression across cancer stages that are expected to be the therapeutic targets [ 21 ]. And in non-small cell lung cancer, some researchers also discovered that mitochondrial NDUFA4L2 protein promotes the vitality of lung cancer cells by repressing oxidative stress, suggesting mitochondrial NDUFA4L2 could represent promising targets for therapy [ 22 ]. Unlike SHMT2, NDUFA4L2 had been reported to be involved in the occurrence and development of kidney cancer.…”
Section: Discussionmentioning
confidence: 99%
“…For hepatocellular carcinoma, Sarathi et al found that NDUFA4L2, CRHBP and PIGU were main genes with monotonic changes of expression across cancer stages that are expected to be the therapeutic targets [ 21 ]. And in non-small cell lung cancer, some researchers also discovered that mitochondrial NDUFA4L2 protein promotes the vitality of lung cancer cells by repressing oxidative stress, suggesting mitochondrial NDUFA4L2 could represent promising targets for therapy [ 22 ]. Unlike SHMT2, NDUFA4L2 had been reported to be involved in the occurrence and development of kidney cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Wherein, activated by HIF1α, NDUFA4L2 inhibited ROS production by the respiratory chain of mitochondria in non-small cell lung cancer cells. Knockdown of NDUFA4L2 promoted an increase in ROS production, apoptosis, and the progression of EMT in the NSCLC cell lines [45]. Apparently, the activation of EMT due to a decrease in the expression level of NDUFA4L2 is a mechanism of its influence on metastasis of ccRCC.…”
Section: Discussionmentioning
confidence: 86%
“…As a component of the ETC complex I subunit, NDUFA4L2 ne-tunes complex I activity, and mediates mitochondrial activation of OXPHOS [45]. COX6B2 facilitates the assembly of complex IV to support mitochondrial respiration and OXPHOS-induced generation of ATP [46]. We also found the upregulation of ATP6V1G2, which encoded subunit G2 of vacuolar ATPase (V-ATPase), transporting protons from the cytoplasm into the lysosome and maintaining lysosomal acidi cation [47].…”
Section: Fp Intervention Promoted Energy Metabolism Of the Colonic Epmentioning
confidence: 80%